The Impact of Low Carb-KETO Diets on CAD-Why more Research is needed - Richard M Fleming; Matthew R Fleming; BS; NRP (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Coronary Artery Disease (CAD) is the result of multiple factors - many of which are now routinely tested for - which interact with each other and the patient to produce an inflammatory effect within the walls of the coronary arteries, impairing the ability of these arteries to increase coronary blood flow when needed. Fundamental to changes in these multiple factors as measured by blood tests, are the effect various diets have when consumed by people for an extended period of time. However, changes in these blood tests are poorly correlated with changes in CAD - limiting our current knowledge about the true effect these diets have on CAD.  This paper takes a look at the only studies, which have looked at the impact of LowCarb-Ketogenic diets (LCKD) on these blood tests and corresponding changes in CAD.